SITUATION AND CONDITIONS OF INTERNATIONAL REFUGEES IN THE PANDEMIC OF COVID-19 (LAW REVIEW OF INTERNATIONAL REFUGEES) - SAKHARINA, IIN KARITA (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Refugees are people who leave their countries and go to other countries to ask for protection. During the Covid-19 pandemic, refugees also became one of the groups affected by the spread of the virus that has claimed many lives almost throughout the country and became a global disaster. Countries that are affected by the spread of this virus are very vulnerable, both susceptible to disease, exposed to the virus are also vulnerable to eviction, especially for a number of countries that apply lockdown. Therefore there needs to be a study that examines the protection and efforts that can be made by countries that are currently accommodating refugees as well as UNHCR as a UN organization that deals with this refugee problem, so that refugees remain protected during this pandemic.